2021
DOI: 10.11124/jbies-21-00207
|View full text |Cite
|
Sign up to set email alerts
|

Clinical interprofessional education in the health professions: a scoping review protocol

Abstract: The objective of this scoping review is to identify, characterize, and summarize evidence from the published literature on clinical interprofessional education.Introduction: Clinical interprofessional education refers to learning within clinical learning environments, such as hospitals, primary care clinics, and long-term care facilities. The learning involves direct interaction with real patients, where learners collaborate to deliver care and improve health outcomes.Inclusion criteria: This scoping review wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The data extracted will include specific details that include the title, author names, date of source, publication year and type, study design, keywords, abstract screening for appropriateness, study setting and population, reported benefits, reported limitations, conclusion, most significant findings, and findings relevant to the review questions. Further to this, extracted data will include the types of clinical learning environments used, the health professions that the involved students belonged to, stipulated learning outcomes, evaluation of the intervention and any measurement tools used 40. The form will be pilot tested by the researcher and research librarian to ensure consistency 29.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data extracted will include specific details that include the title, author names, date of source, publication year and type, study design, keywords, abstract screening for appropriateness, study setting and population, reported benefits, reported limitations, conclusion, most significant findings, and findings relevant to the review questions. Further to this, extracted data will include the types of clinical learning environments used, the health professions that the involved students belonged to, stipulated learning outcomes, evaluation of the intervention and any measurement tools used 40. The form will be pilot tested by the researcher and research librarian to ensure consistency 29.…”
Section: Methodsmentioning
confidence: 99%
“…Further to this, extracted data will include the types of clinical learning environments used, the health professions that the involved students belonged to, stipulated learning outcomes, evaluation of the intervention and any measurement tools used. 40 The form will be pilot tested by the researcher and research librarian to ensure consistency. 29 Any modifications made to the data extraction tool will be stated in the scoping review.…”
Section: Methodsmentioning
confidence: 99%